2013
DOI: 10.4028/www.scientific.net/amr.701.265
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plastic Waste (High Density Polyethylene) in Concrete Mixture as Aggregate Replacement

Abstract: Rapid industrial development causes serious problem all over the world such as depletion of natural aggregates and creates enormous amount of waste material from construction and demolition activities. Quantities of polymer wastes also have been increased these recent years due to the boost in industrialization and the rapid improvement in the standard of living. In Malaysia, most of polymer wastes is abandoned and not recycled. This situation causes serious problems such as wastage of natural resources and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 5 publications
2
18
0
3
Order By: Relevance
“…These results agree with what other researchers reported [35,36,41,55,56]. This decrease could be due to the weak pond between the plastic aggregate and the cement paste since the plastic has a smooth surface which weakens the interfacial transition zone [37,39]. Moreover, plastic is a kind of hydrophobic material (which makes it water-repelling) and this may limit the water required for cement hydration from entering through the structure [44].…”
Section: Compressive Strengthsupporting
confidence: 90%
“…These results agree with what other researchers reported [35,36,41,55,56]. This decrease could be due to the weak pond between the plastic aggregate and the cement paste since the plastic has a smooth surface which weakens the interfacial transition zone [37,39]. Moreover, plastic is a kind of hydrophobic material (which makes it water-repelling) and this may limit the water required for cement hydration from entering through the structure [44].…”
Section: Compressive Strengthsupporting
confidence: 90%
“…The two directions that emerged in practice and research are utilisation of the raw plastic granulate as partial substitute for sand aggregate [1][2][3][4][5] whereby concrete is used as a medium for disposal of polymer waste (in the amounts that do not significantly affect its strength) and the other is the use of processed resins for production of polymer concrete [6,7]. However, knowing that concrete reinforced with commercially available steel or poly-propylene (PP) fibres is a more resilient building material than plain concrete [8,9], another promising option is recycling of plastic for production of fibres to be used as secondary reinforcement for concrete along the traditional steel rebars.…”
Section: Introductionmentioning
confidence: 99%
“…Using recycled material as aggregate in pavement construction reduces the need for virgin or natural aggregates, preserves the environment, and saves landfill space [27]. A key advantage to using waste or recycled materials such as plastics or composite material in concrete is to help reduce the solid wastes being landfilled [28]. The results of previous studies showed that recycled materials (other than the composite material from wind turbine blades) can be incorporated into concrete without detrimental effects [29].…”
Section: Additional Attemptsmentioning
confidence: 99%